The Use of Indicators of Analytical Procedures in Estimating Contracting risk - Zahraa Qaes Jkhyur; Sohad Sabih Alsaffar (Journal of Madenat Alelem University College, 2022)
The main aspect of the research problem is represented in the lack of interest in building a methodology that determines how to deal with contracting risk by using what is provided by the indicators and tools of analytical procedures, as these indicators help in assessing that risk. The aim of the study is represented in the following: 1. Clarify the risk of contracting, and the approved indicators for estimating it. 2. Explain the role of analytical procedures in estimating contracting risk. 3. To propose a methodology for estimating contracting risks, using the indicators of analytical procedures. The research is based on the following hypothesis: "The indicators of analytical procedures help the auditor in assessing the risk of contracting, and choosing the means and tools that can be used to deal with and reduce these risks." The researchers prepared the practical side of the research by conducting an analytical study in one of the Iraqi private banks, the "Iraqi Credit Bank", by adopting a model prepared for this purpose that helps the auditor use the indicators of analytical procedures to assess the risk of contracting, and make a decision to accept or reject the unit under review. The main findings of the research were the following: 1. There is a need for the auditor to take into account the risk of contracting by applying a set of indicators linked to the analytical procedures. 2. The auditor’s understanding of the risk of contracting, through the indicators of the analytical procedures, helps in determining a methodology for dealing and reducing the risk by accepting or rejecting the unit subject to auditing. As well as determining the nature, time and extent of the audit procedures. As for the most prominent recommendations, they were as follows: 1. The need to take into account the risk of contracting to protect the auditor himself from accusations of negligence from external users as a result of the gap between what is expected of my audit performance and professional performance. 2. The necessity to develop an assessment of the risk of contracting through what has been applied in the research using the two indicators of the extent to which external users rely on the financial statements, and the likelihood that the bank will face financial difficulties and crises.